(untitled) (Journal of Comparative & International Higher Education, 2024)
Using the pull-and-push model as a main theoretical framework, this qualitative interview-based study explores the changes in STEM students’ intentions to pursue international mobility in the context of the Russia-Ukraine war and the factors related to students’ mobility decisions in the context of geopolitical tensions. The findings suggest that in situations with military conflict, STEM students are ‘pulled’ and ‘pushed’ to make decisions under the influence of the factors located both on the receiving and domestic sides, and the decisions of whether to pursue international mobility were primarily driven by safety, financial, and social tension concerns. The study’s findings offer some theoretical and practical implications of the changes in student mobility in the context of war conflict for higher education institutions internationally.